Pertanggungjawaban Extrajudicial Killing Dalam Hak Asasi Manusia - Toisuta, Chayenne Rosele Yohana; Peilouw, Johanis Steny Franco; Daties, Dyah Ridhul Airin (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Amnesty International reported that the Myanmar Military in early 2021 carried out executions on the spot without trial or Extrajudicial Killing of more than 1000 Myanmar civilians, after the coup of Aung Sang Su Kyi which turned out to be a crime often committed by government officials in other countries such as the Philippines, Indonesia, and Bangladesh. The purpose of this study is to know and understand Extrajudicial Killing as a violation of human rights and a form of state accountability for perpetrators of Extrajudicial Killing. The research methods that the author uses are normative juridical research methods as well as, legal approach, case approach and conceptual approach. The results that the authors conclude show that Extrajudicial Killing is a violation of human rights as stipulated in the 1948 Universal Declaration of Human Rights, the 1966 International Covenant on Civil and Political Rights, the 1966 International Covenant on Economic, Social and Cultural Rights, the 2016 Minnesota Protocol, the 1998 Rome Statute and the 2013 ASEAN Declaration of Human Rights. Extrajudicial Killing is a violation of the right to life which is a human right protected by the UDHR and ICCPR 1966. Based on this, the perpetrators of extrajudicial killings must be held accountable as stipulated in the Articles of States Responsibility on International Wrongful Acts 2001.